EFFECTS OF THE DRUG "REOAMBRASOL" ON MORPHOLOGICAL CHANGES IN THE SKIN AND LIVER IN EXPERIMENTAL BURN SHOCK - Mirzaanvar Nuridin ugli Ibragimov; Larisa Ivanovna Shevchenko; Khamid Yakubovich Karimov; Azizjon Kosimovich Khaidarov; Dilzoda Yunusovna Ibragimova (Scholar Express Journals, 2022)
Burns continue to be one of the most socially significant aspects of the trauma problem. Despite the progress of combustiology and intensive care, the results of treatment of such patients often remain unsatisfactory. The pathogenetic substantiation and the development of a system of correction of organ dysfunction in patients with extensive deep burn injuries is an urgent task for practical medicine[10]
Keywords: Burn Shock; Morphological Methods Of Research; Infusion Blood Substitute; Rats; Skin